The Counterparty Assessment Mechanism in the Receivables Management System of Agricultural Organizations in the Republic of Belarus and the Ukraine - Sviatlana Shсharbatsiuk; Pelageya Papkovskaya; Kateryna Pylypenko (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The article investigates issues regarding settlements between business counterparts in the Republic of Belarus, including those between Ukrainian and Belarusian enterprises. The presence of bad debts is identified as a key issue, leading to overdue and unrealistic debt collection accounting that burdens a company's balance sheet, resulting in a loss of financial stability of the creditor enterprise. Monitoring of business counterparts helps minimize this risk. Therefore, a mechanism has been developed to collect information about a counterparty and create a credit dossier. There is a proposal to monitor a counterparty's solvency based on criteria that has been specifically established for an industry. The proposed mechanism will help control unjustified growth in the receivables of agricultural organizations in The Republic of Belarus and the Ukraine in hopes of keeping funds in circulation, and reducing the risk of companies losing their own financial stability due to overly loyal credit policies.